Bibliometric Analysis of Hybrid Learning Research Trends in Schools - Emiliyanti, Rantika (CV. Media Inti Teknologi, 2024)
The aim of this research is to examine how research onhybrid learning in schools. This research method uses a literature review using a bibliometric analysis method approach starting from entering the keyword “pembelajaran hybrid” by setting the search year 2018-2023 and journals using the Publish or Perish (PoP) software application. The database used is Google Scholar, after searching Initially by selecting the keyword